#TITLE_ALTERNATIVE# - TANTRA PRATAMA WIBOWO (NIM : 15108026); Pembimbing : Dr. Deni Suwardhi, ST., MT. ; Dr. Soni D, JUNNO
Sugarcane is a monocot grass plant from Poaceae family which generally takes about 11 to 12 months to be ready to harvest, leading to high spatio-temporal variability of the crop development and radiometry. The objective of this research is to understand this variability and subsequently use it to estimate the sugarcane age and its optimum age to be harvested. True color camera and near-infrared camera which are mounted on an unmanned aerial vehicle are used to do the observation. From the near infrared image, vegetation index can be calculated to show the density of green vegetation of specific area. The vegetation index used in this research is Enhanced Normalized Vegetation Index (ENDVI), a mathematical model to obtain vegetation index from single near infrared image. Based on the results of this study it can be found that ENDVI and sugarcane’s age have a fairly high correlation. The correlation between vegetation index value and sugarcane’s age will be used to estimate other sugarcane fields age. Sugarcane’s age estimation couldn’t be done just by using ENDVI value, therefore visual interpretation should be involved. Meanwhile, the correlation of ENDVI value and optimal harvest time is obtained from the brix data.